Краткий очерк становления режущих материалов - Журило, Алла Григорьевна; Журило, Дмитрий Юрьевич; Руднев, Александр Витальевич (ИД "Руда и металлы", 2015)
Рассмотрены первые режущие инструменты из различных сплавов. Представлена современная классификация режущих материалов. В связи с изобретением паровой машины, появилась самостоятельная отрасль промышленности – машиностроение. Это сопровождалось ростом потребления металлических изделий не только для бытовых нужд, но и для удовлетворения запросов промышленности, что вызвало резкое повышение спроса на металл и привело к развитию токарного дела, появлению ткацкого, кузнечно-прессового и другого оборудования. Возникла потребность в различных сталях, в том числе и для режущего инструмента. Улучшение свойств сталей привело к резкому снижению стоимости механической обработки и к значительному расширению применения этого материала в машиностроении и других отраслях.

The first cutting tools made of diff erent alloys have been examined. The modern classifi cation of cutting materials is presented. It is described how machine-building as the individual industrial branch was established as a result of creation of a steam machine. It was accompanied by elevation of consumption of metal products not only for individual customers, but also for satisfaction of industrial demands. In its turn, it has caused strong increase of demand for metal and has led to development of turning technologies, appearance of weaving, forging, pressing and other equipment. Diff erent steels were required for these purposes, i.e. steels for cutting tools. Improvement of properties of these steels stipulated severe decrease of cost of mechanical processing and to substantial expanding of usage of this material in machine-building and other industries.
Brief review of the development of cutting tools
Keywords: сталь; сплав твердый; классификация; история техники; cutting materials; steel; hard alloys; classification